BankCare: A Mobile Complaint Management System for the Banking Sector Using TOPSIS-Based Prioritization - Kayla Nahda Muadzah; Agariadne Dwinggo Samala; Yeka Hendriyani; Titi Sriwahyuni (Sagamedia Teknologi Nusantara, 2025)
Efficient complaint management is critical for maintaining service quality in the banking sector. This study presents BankCare, a cross-platform mobile application developed using the Flutter framework, designed to streamline the handling of customer complaints. The application enables users to submit, edit, and monitor complaints, while administrators can manage, respond to, and prioritize them through a dedicated dashboard. A key feature of BankCare is the integration of the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method, which allows complaints to be automatically prioritized based on urgency level and submission time, supporting objective and data-driven decision-making. Additional features include real-time notifications, user-friendly interfaces, and role-based access control for both users and administrators. Comprehensive testing confirmed the effectiveness, reliability, and usability of core functionalities, including complaint submission, admin responses, and priority-based sorting. User feedback further indicated high levels of satisfaction and ease of interaction. By combining mobile technology with a decision-support algorithm, BankCare offers an intelligent, responsive, and structured solution for optimizing complaint handling in the banking sector.